Pengembangan Aplikasi Augmented Reality untuk Edukasi Keselamatan Kebakaran: Metode Prototyping dan Usability - Setiawan, Ridwan; Rahayu, Sri; Komalasari, Iis (Indonesian Society of Applied Science, 2025)
This study aims to develop an Augmented Reality (AR) application to introduce fire safety equipment as part of Occupational Health and Safety (OHS) education for the general public. The research employed a prototyping method, which involved iterative stages from requirements analysis to user evaluation, as well as functional testing using Black Box Testing and usability testing with 20 respondents. The results showed that all application features functioned according to specifications, and the usability testing yielded a user satisfaction score of 80.1%. These findings indicate that AR is effective as an interactive educational medium to enhance public understanding of fire protection equipment. The implication of this study is the potential for wider use of AR technology in public education to support fire risk mitigation efforts.